Differences in Mathematical Problem-Solving Ability of Grade XI Senior High School Students on Matrix Material Between Educational Card Game-Assisted Strategy and Expository Learning Strategy - Dewi, Nurika Kartika; Yahfizham (Desimal: Jurnal Matematika, 2026)
Mathematical problem-solving ability is a fundamental competency in mathematics education because it enables students to interpret problems, develop solution strategies, implement mathematical procedures, and evaluate the validity of their answers. Although game-based learning has been increasingly incorporated into mathematics instruction, empirical evidence comparing card-assisted educational games with conventional expository instruction for improving students’ mathematical problem-solving ability on matrix material remains limited. This study aimed to examine the difference in mathematical problem-solving ability between Grade XI students taught using a card-assisted educational game strategy and those taught using an expository learning strategy. A quantitative quasi-experimental study employing a pretest-posttest comparison group design was conducted at SMA Swasta IT Ummi Ayuni Perbaungan, Serdang Bedagai Regency, Indonesia, involving 40 students selected through total sampling. Data were collected using a validated mathematical problem-solving test and analyzed using appropriate parametric statistical procedures. The findings revealed that students in the experimental group achieved a higher posttest mean score (80.55) than those in the expository group (67.90), with a statistically significant difference (t(38) = −5.347, p < .001). These findings indicate that the card-assisted educational game strategy provided a more effective learning environment for developing students’ mathematical problem-solving ability on matrix material than the expository learning strategy. The study contributes empirical evidence supporting the integration of structured, non-digital educational games as an effective instructional alternative for secondary mathematics learning.